Two high quality chromosome-scale genome assemblies of female and male silver pomfret (Pampus argenteus) - Jiabao Hu; Youyi Zhang; Yaya Li; Yuanbo Li; Man Zhang; Wanlong Huang; Shanliang Xu; Danli Wang; Xubo Wang; Jing Liu; Yajun Wang; Xiaojun Yan (Scientific Data, 2024)
Abstract Pampus argenteus is a highly commercial marine fish whose population is declining sharply. Here, we generated a female P. argenteus genome, spanning 536.33 Mb with contig N50 of 1.79 Mb; 24070 genes (99.50% of 24,182) were functionally annotated. To improve quality of it, we assembled a 553.79 Mb genome of male fish with contig N50 of 24.75 Mb through HiFi and ultra-long ONT sequence technologies; 550.82 Mb were anchored onto 24 gap-free chromosomes; 22,892 genes (98.1% of 23,346) were functionally annotated; the QV value was 51.55 with 98.9% of BUSCO and 99.39% coverage of Illumina reads. Finally, we compared this genome with previous published one, revealing 37,301 SVs. 52.82 Mb and 18.05 Mb SDs were characterized in our and published assemblies, respectively, and 48.96 Mb PURs were constructed. Thus, this genome assembly exhibits excellent completeness, continuity and accuracy comparing to the published one, which can be current preferred reference genome. Overall, these works help aquaculture and wild resources recovery of P. argenteus and provide a valuable genetic resource for study.